Penerapan Pembelajaran Berbasis Masalah untuk Meningkatkan Pemahaman Siswa terhadap Konsep Dasar Probabilitas - Triyono, Ageng; Maruf, Abdul Hakim (LPPM Universitas Advent Indonesia, 2025)
The purpose of this study was to improve the understanding of class X students towards the concept of probability. The purpose of the study was achieved using a classroom action research method whose action cycle follows the Kemmis & Taggart Model. The classroom action given was the application of a problem-based learning model for 3 cycles. The subjects involved were 12 class X students, the researcher as a teacher, 1 senior teacher as a validator of learning devices and test instruments, and 1 principal as an observer. The research data was taken using a probability concept understanding test instrument in the form of 5 descriptive questions, which were given at the end of each cycle. Learning outcome data were analyzed by calculating the average score and percentage of learning completion. Other data in the form of observer notes were taken using an observation sheet. After the classroom action was carried out, the average score of learning outcomes increased from each cycle, which increased by 33 from cycle I to cycle II, and increased again by 9 from cycle II to cycle III. The application of the problem-based learning model in this study was said to be successful because the achievement of student completion had exceeded 75%, namely in cycles II and III. Thus, the results of this study can be a recommendation for teachers who want to teach the concept of probability.